2008
DOI: 10.1111/j.1532-5415.2008.01822.x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Napping and Sleep in Older Adults: Are Evening Naps “Bad” for Nighttime Sleep?

Abstract: Objectives To compare objective and subjective measurements of napping, and to examine the relationship between evening napping and nocturnal sleep in older adults. Design For twelve days, participants wore actigraphs and completed sleep diaries. Setting Community Participants 100 individuals who napped, 60–89 years (including good and poor sleepers with typical age-related medical comorbidities). Measurements Twelve days of sleep diary and actigraphy provided subjective and objective napping and sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 23 publications
3
50
0
3
Order By: Relevance
“…First, collecting information on daytime napping was accomplished through self-reports in all included studies. Previous studies suggested that older subjects tended to underreport their napping behaviors [43]. Consequently, our meta-analysis might underestimate the risk estimates for the association between daytime napping and mortality.…”
Section: Discussionmentioning
confidence: 79%
“…First, collecting information on daytime napping was accomplished through self-reports in all included studies. Previous studies suggested that older subjects tended to underreport their napping behaviors [43]. Consequently, our meta-analysis might underestimate the risk estimates for the association between daytime napping and mortality.…”
Section: Discussionmentioning
confidence: 79%
“…For example, a patient may develop increased pre-sleep anxiety due to fear of having another night of insomnia (conditioning), or they may use TV or radio to help “relax” or occupy their time while waiting to fall asleep. Others may start to have variable bed times to deal with insomnia or take daytime naps; while naps are generally not recommended for patients with insomnia, for older adults without insomnia complaints, it is important to note that naps have minimal side effects 36 and improve vigilance/performance post-naps. 37 Addressing these perpetuating factors is an important goal of non-pharmacologic insomnia treatment as discussed further below.…”
Section: Insomniamentioning
confidence: 99%
“…The majority of studies that have collected data on bedtime and arising time typically focus on a specific age group (Campbell, Gillin, Kripke, Erikson, & Clopton, 1989;Dautovich, McCrae, & Rowe, 2008;Ishihara, Miyasita, Inugami, Fukuda, & Miyata, 1987;Ohayon & Vecchierini, 2005), although a few studies exist that have included more diverse age groups Hume, Van, & Watson, 1998;Lichstein, Durrence, Reidel, Taylor, & Bush, 2004). Thus, there is a dearth of literature regarding basic behavioral circadian parameters.…”
Section: Introductionmentioning
confidence: 99%